Drinking Water Quality and Its Impact on Community Health Along the Eastern Coast of Ghana. - Kumedzro, S.E. (University of Ghana, 2023)
Diarrhoea is known to be the leading cause of high mortality, which is gotten from the intake of contaminated water and food sources. In Ghana, people are greatly affected by Diarrhea, therefore this research sought to evaluate and measure the quality of drinking water sources in communities along the Eastern coast of Ghana and its impact on human health. Sources of community drinking water which included Pipes, Wells, Poly-tanks and Sachets water in each community were mapped out. A mixed method approach was used from the selection of the sample sites to the analysis of the data obtained. Forty samples were taken from the community drinking water sources, 19 from Anyako, 14 Anyanui and 6 from Atiteti whilst 15 water samples were taken from household drinking water storage containers based on the proportion that drank from the various categories of community drinking water in each study area. Water samples were examined for the presence of Coliform bacteria, Salmonella, Shigella and Enterococcus using the culture media and the buffered dilution water method, and Physiochemical parameters; Total Alkalinity, Nitrate Nitrogen, Phosphate, Sulphate, Calcium, Magnesium, Potassium and Sodium were analysed. Collection & recording information on drinking water sources, ways water is managed and the general health and hygiene was done by observations, questionnaires and interviews with the locals in the study areas. Visits were made to the district assembly and the health centres in each community to gather data on the number of diarrhoea cases throughout the sampling period. The information was manually recorded and inserted in SPSS. The descriptive tool was used to determine the frequencies and percentages of the variables in the questionnaire. Chi square test was executed to find the relationship between two variables. Data from the field and the lab were analysed using Microsoft Excel and a Statistical Package for Social Sciences (SPSS) version 26. Results were recorded in Excel and exported to SPSS for the Two-way Analysis of Variance to be done. The test run to determine the significant changes between the water samples in each month and during the sampling period was the Friedman’s test. Findings indicated no detection of Salmonella, Shigella, Enterococcus and Vibrio cholerae in the water sources. Within the three communities, the Physico-chemical parameters with good levels were dissolved oxygen, total alkalinity and sulphate and sodium. The other parameters recorded levels that were either below or exceeding the WHO standard of drinking water. The microbial quality of the water sources showed poly tank 5 in Anyako, Pipe 3, 2 and 6 in Atiteti as well as Pipe 2, 4 and 5 in Anyanui as the only sources that had no changes in them during the period although statistically, Anyako was the only community to record significant changes within the samples from the water sources. Findings also showed an increase in the E. coli count in the household drinking water in their storage containers than in the community drinking water sources, although this did not account for the high number of diarrhoea cases in each of the community especially in women and in children. This was an indication that the high cases of diarrhoea in Anyako, Atiteti and Anyanui could be due to other predicting factors. The high E. coli counts in the drinking water source at the community level and the household level was a result to the manner by which the residents handled the water as well as poor sanitation and personal hygiene, the cost oof water and their educational level.
MPhil. Environmental Science
Keywords: Diarrhoea; mortality; Ghana; Coliform bacteria